Jejak Pengabaian yang Tak Terlihat: Eksplorasi Pengalaman Emotional Neglect pada Remaja Binaan LPKA Kelas II Payakumbuh - Aditia Rahman; Zakwan Adri (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Emotional neglect is a form of non-physical maltreatment that occurs when a child fails to receive sufficient emotional support, attention, and affection necessary for proper psychological growth. This study aimed to explore the lived experiences of emotional neglect among a male juvenile inmate at the Correctional House for Adolescents (LPKA) Class II Payakumbuh and to understand how these experiences influenced emotional and behavioral development prior to engagement in criminal activities. A qualitative design with a descriptive phenomenological approach was employed, and data were collected through three in-depth interviews with a 17-year-old participant who had experienced emotional neglect since childhood. Analysis was conducted using Interpretative Phenomenological Analysis (IPA) stages. Findings revealed that emotional neglect caused deep emotional wounds, persistent loneliness, family disintegration, and emotional escape through deviant behaviors, including drug use and also criminal acts. The participant also expressed a profound emotional longing for his mother and attempted to reconstruct his self-identity by seeking supportive relationships outside the family environment. The study emphasizes the critical importance of emotional care in parenting and highlights the need for systemic interventions and support for children raised in dysfunctional families to prevent the development of maladaptive behaviors and to promote healthier emotional and social development.